Analysis of Personal Taxpayer's Compliance Level in Reporting Annual Income Tax SPT Year 2018-2020 (Case Study of Pratama Tax Service Office Padang Dua) - Ardiany, Yuli (Dinasti International Journal of Economics, Finance & Accounting, 2022)
Analysis of the level of compliance of individual taxpayers in reporting the Annual Tax Return is an activity to assess the level of compliance of individual taxpayers in fulfilling their tax obligations and exercising their tax rights. The type of research is descriptive quantitative research by tracing the level of compliance of individual taxpayers in reporting the Annual Income Tax Return at the Padang Dua Pratama Tax Service Office, from 2018 to 2020. The results of the study were obtained from 2018 to 2020 with fluctuating compliance levels. or less stable, some have increased and some have decreased. This is partly due to the lack of awareness of taxpayers in fulfilling their tax rights and obligations. Efforts made by the Padang Dua Pratama Tax Office in improving taxpayer compliance are providing counseling about taxation, holding a Tax Center.